Missing the sweet spot: one of the two N-glycans on human Gb3/CD77 synthase is expendable. (8th May 2021) - Mikolajczyk, Krzysztof; Bereznicka, Anna; Szymczak-Kulus, Katarzyna; Haczkiewicz-Lesniak, Katarzyna; Szulc, Bozena; Olczak, Mariusz; Rossowska, Joanna; Majorczyk, Edyta; Kapczynska, Katarzyna; Bovin, Nicolai; Lisowska, Marta; Kaczmarek, Radoslaw; et al.
Abstract: N-glycosylation is a ubiquitous posttranslational modification that may influence folding, subcellular localization, secretion, solubility and oligomerization of proteins. In this study, we examined the effects of N-glycans on the activity of human Gb3/CD77 synthase, which catalyzes the synthesis of glycosphingolipids with terminal Galα1→4Gal (Gb3 and the P1 antigen) and Galα1→4GalNAc disaccharides (the NOR antigen). The human Gb3/CD77 synthase contains two occupied N-glycosylation sites at positions N121 and N203 . Intriguingly, we found that while the N-glycan at N203 is essential for activity and correct subcellular localization, the N-glycan at N121 is dispensable and its absence did not reduce, but, surprisingly, even increased the activity of the enzyme. The fully N-glycosylated human Gb3/CD77 synthase and its glycoform missing the N121 glycan correctly localized in the Golgi, whereas a glycoform without the N203 site partially mislocalized in the endoplasmic reticulum. A double mutein missing both N-glycans was inactive and accumulated in the endoplasmic reticulum. Our results suggest that the decreased specific activity of human Gb3/CD77 synthase glycovariants resulted from their improper subcellular localization and, to a smaller degree, a decrease in enzyme solubility. Taken together, our findings show that the two N-glycans of human Gb3/CD77 synthase have opposing effects on its properties, revealing a dual nature of N-glycosylation and potentially a novel regulatory mechanism controlling the biological activity of proteins.